Cytotoxicity of thymus vulgaris essential oil towards human oral cavity squamous cell carcinoma - Sertel, Serkan; Eichhorn, Tolga; Plinkert, Peter K.; Efferth, Thomas (Anticancer research, 2011)
Background: Oral cavity squamous cell carcinoma (OCSCC) accounts for 2% to 3% of all malignancies and has a high mortality rate. The majority of anticancer drugs are of natural origin. However, it is unknown whether the medicinal plant Thymus vulgaris L. (thyme) is cytotoxic towards head and neck squamous cell carcinoma (HNSCC). Materials and Methods: Cytotoxicity of thyme essential oil was investigated on the HNSCC cell line, UMSCC1. The IC50 of thyme essential oil extract was 369 μg/ml. Moreover, we performed pharmacogenomics analyses. Results: Genes involved in the cell cycle, cell death and cancer were involved in the cytotoxic activity of thyme essential oil at the transcriptional level. The three most significantly regulated pathways by thyme essential oil were interferon signaling, N-glycan biosynthesis and extracellular signal-regulated kinase 5 (ERK5) signaling. Conclusion: Thyme essential oil inhibits human HNSCC cell growth. Based on pharmacogenomic approaches, novel insights into the molecular mode of anticancer activity of thyme are presented.